Recruiting foreign-born individuals who have sought an abortion in the United States: Lessons from a feasibility study - Zuniga, Carmela; Ragosta, Sachiko; Thompson, Terri-Ann (Frontiers in Global Women's Health, 2023)
Although studies have documented challenges people encounter when attempting to access abortion care in the United States, there is little research on the perspectives and experiences of foreign-born individuals, who may encounter unique barriers to accessing care. Since lack of data may be due to difficulty recruiting this population, we explored the feasibility of using social media to recruit foreign-born individuals who have sought an abortion into interviews to share their abortion experiences. Our target population was limited to English and Spanish-speakers due to budget constraints. As this recruitment method was unsuccessful, we attempted to recruit our target population through the crowdsourcing website, Amazon Mechanical Turk (mTurk)to take a one-time survey on their abortion experience. Both online recruitment methods yielded a significant number of fraudulent responses. Although we aimed to collaborate with organizations that work closely with immigrant populations, they were unavailable to assist with recruitment efforts at the time of the study. Future abortion research utilizing online methods to recruit foreign-born populations should consider incorporating information on their target populations’ use of online platforms as well as cultural views on abortion in order to develop effective recruitment strategies.